Relationship Between Body Weight and Linear Measurement with Udder Volume in Fat Tailed Sheep in Sumenep, Madura - Rohman , D. R.; Maylinda, Sucik (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2024)
The aim of the research was to determine the relationship between between body weight, linear measurements, and udder volume in fat-tailed sheep. Material used in this reseach were 120 female fat- tailed sheep (DEG) with the range of the age PI1 to PI4. Method used in this research was cases study a with direct measurement in the field. Variables observed were chest girth, body length, body height, body weight, and udder volume. Data were analyzed using simple correlation and linear regression analysis. Results showed that the correlation between body weight and udder volume was significant (P < 0.05). With a corelation coefficient 0.687 (R2 47.2%). The function of regression equation is Y=509.05481+ 5.28X. The coefficient of correlation and coeffision of determination between vital statistics and udder volume is low, on chest circumference 0.429 (18.41%), body length 0.221 (4.88%), and shoulder height 0.2 (4%). Moreover, the regression equation values for chest circumference, body length, and shoulder height are Y = 676,3112-5,44X, Y = 495,6451-2.94X and Y = 495,4974-2,91X, respectively. It can be concluded the udder volume has a positive relationship with body weight, while udder volume have a weak relationship with linear measurements